2022
DOI: 10.1111/all.15331
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the levels of CTLA‐4‐dependent biological defects in patients with LRBA deficiency and CTLA‐4 insufficiency

Abstract: Background Lipopolysaccharide‐responsive beige‐like anchor protein (LRBA) deficiency and cytotoxic T‐lymphocyte protein‐4 (CTLA‐4) insufficiency are recently described disorders that present with susceptibility to infections, autoimmunity, and lymphoproliferation. Clinical and immunological comparisons of the diseases with long‐term follow‐up have not been previously reported. We sought to compare the clinical and laboratory manifestations of both diseases and investigate the role of flow cytometry in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have reported variable immune cell phenotypes in patients with CTLA-4 haploinsufficiency. 7,8 While a minority of patients had reduced absolute counts of total CD3+ cells, a majority of patients had no changes in total CD3 + , CD4 + , or CD8 + T-cell frequencies compared with healthy controls. 7,8 Our data are consistent with these findings (Figure S2A).…”
Section: Deep Immunophenotyping Shows Altered Immune Cell Subsets In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported variable immune cell phenotypes in patients with CTLA-4 haploinsufficiency. 7,8 While a minority of patients had reduced absolute counts of total CD3+ cells, a majority of patients had no changes in total CD3 + , CD4 + , or CD8 + T-cell frequencies compared with healthy controls. 7,8 Our data are consistent with these findings (Figure S2A).…”
Section: Deep Immunophenotyping Shows Altered Immune Cell Subsets In ...mentioning
confidence: 99%
“…Recently, patients with clinically symptomatic CTLA-4 haploinsufficiency were found to have increased frequencies of CXCR5 + PD1 + follicular helper T cells (Tfh) that normalized with abatacept therapy. 8,12 Our study did not include PD-1 or ICOS staining and therefore may be examining different cell populations. Further…”
Section: Deep Immunophenotyping Shows Altered Immune Cell Subsets In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a detailed clinical examination and ordered laboratory tests, including complete blood cell count, serum immunoglobulin levels, and lymphocyte immunophenotyping of whole blood (CD3 + T, CD3 + CD4 + T, CD3 + CD8 + T, CD19 + B, CD16 + CD56 + NK, and CD4 + CD45RA + CD31 + T cells (RTE -recent thymic emigrants). Peripheral B cells were classi ed into three distinct populations: naive mature B cells (CD19+CD27-IgD+), non-classswitched memory B cells (NCS B -CD19+CD27+IgD+), and class-switched memory B cells (CS B -CD19+CD27+IgD-) (24)(25)(26).…”
Section: Clinical and Immunological Evaluationsmentioning
confidence: 99%
“…However, some patients with LRBA gene defects may have normal LRBA protein expression on flow cytometry. 1 , 5 , 6 Knowing these restrictions, we used Sanger sequencing to diagnose the patient and analyzed flow cytometric LRBA protein expression for functional confirmation.…”
mentioning
confidence: 99%